No effect of treatment with intravenous ganciclovir on Epstein‐Barr virus viremia demonstrated after pediatric liver transplantation. (26th June 2017) - Østensen, Anniken B.; Sanengen, Truls; Holter, Ellen; Line, Pål‐Dag; Almaas, Runar
Abstract: EBV after pediatric LT is a risk factor for PTLD. We wanted to evaluate the effect of intravenous ganciclovir on EBV viremia and to identify risk factors for chronic EBV viremia. All pediatric patients who underwent LT in Norway from 2002 until 2015 were reviewed. Twenty‐two of 38 patients with viremia were treated with intravenous ganciclovir for a median of 22 (21‐38) days. Treated and untreated patients were not different with respect to EBV seroconversion prior to transplantation or age at transplantation, but treated patients had significantly earlier viremia after transplantation ( P =.005). There was no difference in the proportion of patients with reduction in virus load in patients treated with ganciclovir compared to untreated patients at 8 weeks. After 1 year, five of 19 patients treated with ganciclovir and six of 14 untreated patients had reduced virus load compared to start of viremia ( P =.27). In conclusion, treatment with intravenous ganciclovir did not change the proportion of patients with reduction in EBV load at 8 weeks and 1 year after viremia. Younger age at transplantation, short time from transplantation to viremia, and lack of EBV seroconversion prior to transplantation were significant predictors of chronic EBV viremia.